Strategi Branding Rockologist, Menjaga Loyalitas Konsumen dengan Mengabadikan Kisah Hidup dalam Wujud Perhiasan Buatan Tangan - Nur Hidayatullah, Ayu Azizah Kusumawati (Master of Management Diponegoro University, 2025)
This research discusses the branding strategy of Rockologist, a handmade jewelry brand from Yogyakarta, which puts forward the concept of “groundedness” to maintain customer loyalty. By connecting consumers with places, people and the past, Rockologist creates jewelry that is not only unique but also holds the customer's life story. Through strong narratives and local artisans' empowerment, the brand builds a deep emotional connection with its consumers. This research uses a qualitative approach with in-depth interviews to understand the consumer experience and the products' impact. The results show that handmade jewelry's emotional and historical value can increase consumer satisfaction and loyalty.